Assessment of changes in the structure land use in Tra Vinh province under the scenarios of climate change and sea level rise - Phuong, Tran Ha; Hung, Hoang Phi; Hung, Nguyen Thanh; Man, Duong Ba; Mon, Danh; Vinh, Dang Hoa; Thuc, Pham Thi Bich; Thuong, Tran Van; Ninh, Nguyen Trung; Phuong, Tran Anh; Long, Ngo Hoang Dai (Vietnam Journal of Science and Technology, 2020)
Currently, in the context of climate change, droughts, salinity intrusion, sea level rise etc. and through the reality, it can be seen that the structure of land use (land use) in Tra Vinh province has been impacted quite strongly. The salinity intrusion, flooding and drought have increased in recent years, requiring appropriately comprehensive and proactive solutions. First and foremost, it’s a solution to change the structure of land use in combination with the change of seed structure and crop production structure to ensure efficient and sustainable development. For an overview of these changes as well as predictions for later years, the assessment of the impact of sea level rise on the average scenario (2030) affects the structure of land use by 2030 compared to the land use data in Tra Vinh in 2016, the results show that the areas flooded under the scenario of climate change and sea level rise RCP6.0  in 2030 are at risk of land use change.[TT1]  The land area has the risk of land use change in the whole province is nearly 24,235 ha. In which the most affected land area is specializing in rice land occupies 71%, area aquaculture (11%), paddy land remaining (8%), especially 4% of residential land in rural areas will be affected, this will directly affect the lives of people in the shallow village. [TT1]Need to revise